Customers\' Loyalty And Word Of Mouth In ECommerce A Study On Malaysia Online Users - Zarandi, Arezoo Amiri (2011)
Opinion the emergence of the Internet and Web has turned a revolution in marketing and selling products and services. The effect of the Internet and Web lead to create an electronic marketplace where products, services, and their related features are presented without any limitation. Consequently, the presence in virtual marketplace became a strategic necessity for corporations. EC can cover product selling process as well as offering after sale services.